The Efficacy of Eye Movement Desensitization and Reprocessing in Children and Adults Who Have Experienced Complex Childhood Trauma: A Systematic Review of Randomized Controlled Trials - Chen, Runsen; Gillespie, Amy; Zhao, Yanhui; Xi, Yingjun; Ren, Yanping; McLean, Loyola (Frontiers in Psychology, 2018)
Background: Survivors of complex childhood trauma (CT) such as sexual abuse show poorer outcomes compared to single event trauma survivors. A growing number of studies investigate Eye Movement Desensitization and Reprocessing (EMDR) treatment for posttraumatic stress disorder (PTSD), but no systematic reviews have focused on EMDR treatment for CT as an intervention for both adults and children. This study therefore systematically reviewed all randomized controlled trials (RCTs) evaluating the effect of EMDR on PTSD symptoms in adults and children exposed to CT. Methods: Databases including PubMed, Web of Science, and PsycINFO were searched in October 2017. Randomized controlled trials which recruited adult and children with experience of CT, which compared EMDR to alternative treatments or control conditions, and which measured PTSD symptoms were included. Study methodology quality was evaluated with Platinum Standard scale. Results: Six eligible RCTs of 251 participants were included in this systematic review. The results indicated that EMDR was associated with reductions in PTSD symptoms, depression and/or anxiety both post-treatment and at follow-up compared with all other alternative therapies (cognitive behaviour therapy, individual/group therapy and fluoxetine) and control treatment (pill placebo, active listening, EMDR delayed treatment and treatment as usual). However, studies suffered from significant heterogeneity in study populations, length of EMDR treatment, length of follow-up, comparison groups, and outcome measures. One study had a high risk of bias. Discussion: This systematic review suggests that there is growing evidence to support the clinical efficacy of EMDR in treating CT in both children and adults. However, conclusions are limited by the small number of heterogenous trials. Further RCTs with standardized methodologies, as well as studies addressing real world challenges in treating CT are required.